Development and evaluation of a search-and-rescue robot Paripreksya 2.0 for WRS 2020. (2nd November 2022) - Megalingam, Rajesh Kannan; Vadivel, Shree Rajesh Raagul; Rajendraprasad, Anandu; Raj, Akhil; Baskar, Siddharth; Balasubramani Marutha Babu, Ragavendra
ABSTRACT: In recent years, the influence of robotics in search-and-rescue missions has become relevant. Robots can provide human rescue teams with valuable information about the disaster area, track victims and speed up the rescue operation. The disaster robot category challenge at the World Robot Summit (WRS) is a platform where emerging technologies in search-and-rescue robot developments are evaluated. This paper describes the design, development and implementation of a teleoperated all-terrain search-and-rescue robot, Paripreksya 2.0, for participation in the Standard Disaster Challenge. The robot was integrated with a 4-DoF robotic manipulator for performing dexterity tasks along with tracks and four assistive flippers for locomotion. The design of the robot was done in SolidWorks and the stability constraints of the robot while climbing stairs and slopes are also calculated. The software of the robot was built on the ROS framework. The robot was designed to perform various tasks including staircase climbing, negotiation of obstacles, opening and closing of valves, manoeuvring, plant inspection, etc. Our team has secured the best-in-class dexterity award at the WRS 2020 challenge. The performance of the robot was evaluated using the scores from different challenges held at the WRS competition. GRAPHICAL ABSTRACT: UF0001